Presenting the model of realizing the right to the city based on the network analysis process (ANP) in the raw-towns of West Mazandaran - Reza Soltanmaleki; Masoud Elahi; Zohreh Davodpour (تحقیقات کاربردی علوم جغرافیایی)
Idealism for urban living necessitates the establishment of infrastructure and a platform that considers all stakeholders, including managers, planners, and citizens, regardless of their social and economic backgrounds, social class, gender, etc. This concept is encapsulated in the notion of the right to the city. However, implementing this concept can pose challenges in smaller cities with more unfavorable conditions. Hence, this research aims to introduce a model for actualizing the right to the city based on the Analytical Network Process (ANP) in the rural cities of western Mazandaran. The current study is categorized as applied research. The statistical population for this study comprised urban experts (chosen through the Delphi technique with a sample size of 25). Alongside on-site observations, information was gathered utilizing the fundamental maps of the country's mapping organization and studies focusing on the three cities of Baldeh, Kejur, and Pol (Kham-shahrs in the western part of Mazandaran province). The Analytical Network Process (ANP) method was employed to process and analyze the data, leading to the extraction of a balanced supermatrix using the Super Decision software. Following various steps, the final priorities of indicators and options for realizing the right to the city were determined. The results of the network analysis (ANP) of the dimensions of realizing the right to the city in the western cities of Mazandaran province indicate that the physical-biological dimension holds the highest weight and importance (0.1970). It is trailed by the economic dimension (0.1725) and the social and cultural dimensions (with a final weight of 0.0847). Among the criteria for realizing the right to the city in the western cities of Mazandaran province, the right to self-determination carries the most significance with a weight of 0.1461, followed by environmental rights (0.0943) and the right to a sustainable city economy (0.0840).